Application of Machine Learning in Survival Analysis - Kutukov, Nikolay (2025)
This bachelor thesis focuses on the application of machine learning algorithms in the domain of survival analysis. The aim is to conduct a comparative analysis between classical survival analysis approaches and modern machine learning algorithms, assessing their performance and interpretability.